Implementation of Ahlu Sunnah Wal Jamaa’ah An-Nahdliyah (ASWAJA) Learning In Building Akhlakul Karimah - Imama, Nur; Djamaluddin, Burhan; Zakariyah, Zakariyah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This article delves into the implementation of Ahlu Sunnah Wal Jamaa’ah An-Nahdliyah (ASWAJA) learning as a foundational strategy for instilling akhlakul karimah (noble character) among students. The cultivation of akhlakul karimah is integral to Islamic education, yet its effective integration into contemporary educational settings remains a challenge. This study aims to elucidate the planning, execution, evaluation, and factors influencing ASWAJA learning's role in fostering akhlakul karimah among students at MTs Abu Amr Tambakrejo Pasrepan. Employing a qualitative approach, data were gathered through interviews, observations, and documentation. Analysis utilized qualitative descriptive methods encompassing data reduction, presentation, and conclusion drawing. Findings reveal the employment of lecture and Drill methods in ASWAJA learning, enhancing students' knowledge retention. Furthermore, teachers exemplify karimah characteristics, supported by requisite training, aiming to mobilize Nahdliyin citizens. Assessment criteria ensure academic standards, with reported results exceeding an 80% KKM threshold. Tasyuf materials within the curriculum impart messages on personal, social, religious, and national life, aiming to cultivate tolerance, balance, and a commitment to Amar Ma'ruf Nahi Munkar among MTs Abu Amr Tambakrejo graduates. This research offers valuable insights into the effective integration of ASWAJA learning to instill akhlakul karimah, thereby contributing ideas to address present and future challenges in Islamic education.